Incidence of extrapleural malignant mesothelioma and asbestos exposure, from the Italian national register. Issue 11 (25th August 2010) - Marinaccio, Alessandro; Binazzi, Alessandra; Di Marzio, Davide; Scarselli, Alberto; Verardo, Marina; Mirabelli, Dario; Gennaro, Valerio; Mensi, Carolina; Merler, Enzo; De Zotti, Renata; Mangone, Lucia; Chellini, Elisabetta; et al.
Abstract : Objectives: The epidemiology of extrapleural malignant mesothelioma is rarely discussed and the risk of misdiagnosis and the very low incidence complicate the picture. This study presents data on extrapleural malignant mesothelioma from the Italian National Mesothelioma Register (ReNaM). Methods: ReNaM works on a regional basis, searching for cases and interviewing subjects to investigate asbestos exposure. Classification and code criteria for certainty of diagnosis and exposure modalities are set by national guidelines. Between 1993 and 2004, 681 cases were collected. Incidence measures and exposure data refer to the ReNaM database. Age-standardised rates were estimated by the direct method using the Italian resident population in 2001. Correlations between the incidence of pleural and non-pleural malignant mesothelioma for the 103 Italian provinces were analysed. Results: Standardised incidence rates (Italy, 2004, per million inhabitants) were 2.1 and 1.2 cases for the peritoneal site (in men and women, respectively), 0.2 cases for the tunica vaginalis testis, and 0.1 in the pericardial site, varying widely in different parts of the country. Mean age at diagnosis for all extrapleural malignant mesothelioma cases was 64.4 years and the men/women ratio was 1.57:1. Median latency was over 40 years for all extrapleural sites combined. The correlation between pleural and peritoneal mesothelioma was 0.71 (Pearson's r coefficient, p<0.001). Modalities of exposure to asbestos fibres were investigated for 392 cases. Conclusions: The rarity of the disease, the low specificity of diagnosis and difficulties in identifying the modalities of asbestos exposure call for caution in discussing aetiological factors other than asbestos.